Pleistocene Bison Skeleton (Bison bison cf. occidentalis) from Clayhurst Crossing, British Colombia - Apland, Brian; Harington, Charles (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1994)
ABSTRACTRemains of a large old male bison skeleton from a gravel pit near Clayhurst Crossing are tentatively referred to the extinct western bison (Bison bison cf. occidentalis). It is the most complete late Pleistocene "medium-horned" bison so far reported from Canada, and is therefore described in detail. Four accelerator mass spectrometry (AMS) radiocarbon dates on bone from the specimen provide a weighted average age of 10,500±90 yr BP, supporting an earlier suggestion that river terraces in the mid-Peace area began developing before 10,000 years ago. Evidently Bison bison antiquus occurred in southern Alberta about 11,000 years ago, and both it and Bison bison occidentalis occupied the Peace River area shortly before 10,000 years ago. It is hypothesised that by at least 9700 BP, B. b. occidentalis had spread southern Alberta. These data suggest that biotic interchange between the former Beringian refugium and the southern interior Plains of North America occurred prior to 10,500 years ago.